2016
DOI: 10.3390/proteomes4020017
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis and Muscle Energy Metabolism Are Modified in HspB1-Null Mice

Abstract: Hsp27—encoded by HspB1—is a member of the small heat shock proteins (sHsp, 12–43 kDa (kilodalton)) family. This protein is constitutively present in a wide variety of tissues and in many cell lines. The abundance of Hsp27 is highest in skeletal muscle, indicating a crucial role for muscle physiology. The protein identified as a beef tenderness biomarker was found at a crucial hub in a functional network involved in beef tenderness. The aim of this study was to analyze the proteins impacted by the targeted inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Compensation which may be elicited by other small Hsps has probably occurred during early development and postnatal life. Consistently we previously reported changes in the status of sHsps in the muscles of the HspB1 -/- mouse [ 36 , 37 ] that may support functional redundancy. However we report here specific characteristics of the HspB1 -/- mouse: a gender dimorphism with marked effects in males, an effect on body weight with no obvious changes in the growth rate, a lower plasma lipids profile, and an alteration of muscle ultrastructure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Compensation which may be elicited by other small Hsps has probably occurred during early development and postnatal life. Consistently we previously reported changes in the status of sHsps in the muscles of the HspB1 -/- mouse [ 36 , 37 ] that may support functional redundancy. However we report here specific characteristics of the HspB1 -/- mouse: a gender dimorphism with marked effects in males, an effect on body weight with no obvious changes in the growth rate, a lower plasma lipids profile, and an alteration of muscle ultrastructure.…”
Section: Discussionsupporting
confidence: 89%
“…However, as we examined animals only postnatally we cannot exclude that the muscles of the mutant mouse could have developed slower than those of wild-type during foetal development. Interestingly, very specific differences between mutants and wild-type controls were detected at the protein level [ 37 ]. The electrophoretic profiles of m. Soleus proteins showed differences in myofibrillar proteins, especially the presence of a putative developmental MyHC isoform which remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Following the procedure used by ( Gagaoua et al, 2015b ), a correlation between biomarkers (strength and sign) was considered robust if it existed at the same time and in the same direction for each of the five muscles. Networks describing cellular processes of the conversion of muscle into meat are very scarce ( Gagaoua et al, 2015b ; Picard et al, 2016 ). Thus, the interpretation of the consistent correlations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study by our group showed that it is at a crucial hub in a functional network involved in beef tenderness ( Guillemin et al, 2011a ). In HspB1 -null mice, comparative proteomics in Tibialis anterior muscle comparatively to the littermate controls showed that the proteins impacted by the absence of HSP27 belong mainly to calcium homeostasis (DRL and CALSQ1), contraction (TnnT3), energy metabolism (TPI1, MDH1, PDHB, CKM, PYGM and APOA1) and Hsp proteins family (HspA9) ( Picard et al, 2016 ). The negative correlation observed in the present study between HSP27 and slow oxidative proteins such as TNNT1, is in accordance with the data of these authors ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study we could not quantify changes in the 469 abundance of muscle proteins involved in calcium homeostasis, such as sarcalumenin or 470 calsequestrin-1, that were not separated in the 1D SDS-PAGE gels. These proteins have 471 recently been detected by 2D-electrophoresis in mice muscle by Picard et al (2016) 472 who found that its abundance in the Tibialis anterior muscle (fast glycolytic) increased 473 in the absence of Hsp27 (heat shock protein that has been described as beef tenderness 474 biomarker, by the group of Picard).…”
mentioning
confidence: 99%